Moving Against the Tide of Exclisivity: Identity Narrative Study of of a Graduate with Visual Impairment - K. C. Nwosu; C. N. Ementa (University of Sofia, 2018)
Modern trend in educating persons with special needs points to the direction of inclusivity and demands the elimination of all forms of educational barriers that can impede their academic successes. However, there appears to exist an entrenched discrimination against persons living with special needs in Nigeria. This warrants they put in extra efforts for them to progress in their academic pursuit. The study explored the identity narrative of a graduate with visual impairment from a Nigerian University with particular reference to his encounters with societal challenges from his early childhood till when he graduated and how he made sense of his everyday world. The qualitative research paradigm was adopted in this study using semi-structured interview as the primary data tool. The narrative inquiry was used during the interview. Data analysis was based on content analysis. Findings indicated that there was the emergence of both desired and undesired identities in his narratives and in spite of the overwhelming challenges our participant faced, the desire for uncommon success is found in his narratives and he actively turned negative challenges in his way into steps that helped him arrive at his desired destination exemplifying an agentic role in constructing meaning in his social world. It was concluded from the study that ability to positively reconstruct ones' negative experiences could lead to self-fulfillment. Resilience and belief in his abilities in spite of crushing experiences are keys to unlocking the potentialities of our respondent.